Kompetensi Manajerial Kepala Sekolah Dalam Mengembangkan Pendidikan Agama Islam Berwawasan Multikultural - Nur Fauziah (J-MPI (Jurnal Manajemen Pendidikan Islam), 2018)
The purpose of this study was to describe and analyze about: 1) Principal planning in developing multicultural Islamic religious education in the 1 Kademangan Vocational High School (SMKN). 2) The process of organizing school principals in applying multicultural Islamic religious education at 1 Kademangan Vocational High School. 3) Implementation Procedure of the principal in developing multicultural Islamic religious education at 1 Kademangan Vocational High School. 4) Control of principals in developing multicultural Islamic religious education in 1 Kademangan Vocational High School. The type of research conducted is qualitative research with a qualitative descriptive approach. This study focuses on managerial competencies of principals in developing multicultural Islamic religious education in 1 Kademangan Vocational High School. For data collection techniques, researchers conduct interviews, documentation and direct observation. While the analysis of the data used in this study is the data analysis technique of the Spradley model or better known as Cyclic mode. The results found by researchers in the field are planning processes, goals must be made clearly because it is used as a guideline for activities that reinforce the direction and effort of activities and facilitate in obtaining the support of resources and competencies in both the organization and the environment. Organizing is organized on the basis of predetermined objectives and formal formal mechanisms in the organizational structure that reflect the needs and optimization of existing resources in a good organization. At the stage of implementing the communication skills of the school principal also determines the course of effective management. The supervision process becomes an important part that is directly related to considering changes in procedures, policies, and even organizational goals.